2017
DOI: 10.1007/s13205-017-0602-3
|View full text |Cite
|
Sign up to set email alerts
|

Crop specific plant growth promoting effects of ACCd enzyme and siderophore producing and cynogenic fluorescent Pseudomonas

Abstract: Fluorescent Pseudomonas, aerobic, Gram-negative bacteria possess many traits that make them well suited as biocontrol and growth promoting agents. Our study revealed that isolates vary in mechanisms involved in the antagonist interactions against pathogen and growth stimulatory effects on host plant. Most of the potential antagonistic fluorescent Pseudomonas identified were avid iron chelators (P233, P201, 176, P76 and, P76). Wide variation in ACCd enzyme production was observed. ACCd enzyme assay tested P141 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 31 publications
(26 reference statements)
0
11
0
Order By: Relevance
“…Siderophores, low molecular weight iron chelators, produced by various soil microorganisms, bind Fe 3+ and make it available for their own growth and also for plants. There are several reports describing the production of siderophores by the rhizospheric micro flora enhancing the iron uptake of plants (Kotasthane et al, 2017; Priyanka et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Siderophores, low molecular weight iron chelators, produced by various soil microorganisms, bind Fe 3+ and make it available for their own growth and also for plants. There are several reports describing the production of siderophores by the rhizospheric micro flora enhancing the iron uptake of plants (Kotasthane et al, 2017; Priyanka et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In other study, Yaghoubi Khanghahi et al (2018a) showed that rice plants inoculated with KSB had higher K concentration in grain as compared to the noninoculated plants. Previous investigations have shown that the nutrient uptake by rice plant was in response to inoculations with K-solubilizing microorganisms signifantly increased through both direct (the ability of solubilizing insoluble silicate compounds minerals in the rhizosphere and plant hormone production) and indirect mechanisms (synthesis of antibiotics, enzymes, fungicidal compounds, and competition with detrimental microorganisms) (Bakhshandeh et al 2015, Priyanka et al 2017.…”
Section: Discussionmentioning
confidence: 99%
“…Some PGPRs are able to produce the 1-aminocyclopropane-1-carboxylate deaminase (ACCd) [ 132 , 133 ], which degrades ACC, the direct precursor of ethylene [ 134 ]. The bacterial ACCd degrades the ACC into ammonium and α-ketobutyrate and, thus, reduces the amount of plant ethylene ( Figure 5 ; [ 85 ]).…”
Section: Wheat Drought Acclimation By Pgprsmentioning
confidence: 99%